2004
DOI: 10.17221/5696-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The effects of diet supplemented with sodium bicarbonate upon blood pH, blood gases and eggshell quality in laying geese

Abstract: The effects of diet supplemented with sodium bicarbonate (NaHCO<sub>3</sub>) upon blood pH, blood gases and eggshell quality during the laying cycle in geese were investigated. Fourteen geese aged 2 yr old were divided into two groups as; control (Group C, n = 7) and 0.5% NaHCO<sub>3 </sub>-supplemented group (Group T, n = 7). After 15&nbsp;days of adaptation period, blood samples were collected every 6 h during a single laying cycle (over 42 h) and the data obtained were analysed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…In the present study, the resting bird's venous blood chemistry values were within the range reported by Martin et al (21). The blood pH of 7.41 and 7.40 in K-and K+-fed birds, respectively, were consistent with a homeostasis condition, and the data agreed with (31), that reported blood pH values of 7.40. There were no differences found in blood pH in the present study; however, the numerical difference between the pH could not be ignored.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the resting bird's venous blood chemistry values were within the range reported by Martin et al (21). The blood pH of 7.41 and 7.40 in K-and K+-fed birds, respectively, were consistent with a homeostasis condition, and the data agreed with (31), that reported blood pH values of 7.40. There were no differences found in blood pH in the present study; however, the numerical difference between the pH could not be ignored.…”
Section: Discussionsupporting
confidence: 91%
“…-concentration (HCO3 -, mmol/l), were determined by the Rapid Lab 248 pH/Blood Gas Analyzer (Kaya et al, 2004). Plasma Na + and K + concentration were detected by using clinical flame photometer, whereas plasma calcium and potassium concentration were determined by atomic absorption spectrophotometer as described by AOAC (2010) using available commercial kit.…”
Section: Methodsmentioning
confidence: 99%
“…Supplementation of sodium bicarbonate may help to maintain proper pH balance, eliminate acidosis and facilitate metabolic process, ensuring maximum growth and productivity Naseem et al, 2005). Moreover, its use as dietary supplement may help rise in blood bicarbonate ion concentration, which can favor better performance of birds (Kaya et al, 2004;Naseem et al, 2005). Information regarding potential beneficial effects of this substance on blood profile of layers during heat stress/summer is scanty, especially in the areas of Asiatic region.Based upon scientific information available, it can be envisaged that high environmental temperature can negatively influence blood profile in poultry birds.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly added as a simple solution for restoring the pH of water that has a high level of chlorine (Whiting et al, 1991). Sodium bicarbonate in feed or water has shown potential benefits on production performance (Ahmad et al, 2005;Khattak et al, 2012;Peng et al, 2013), egg characteristics (Kaya et al, 2004;Jiang et al, 2015) and blood profile (Kurtoglu et al, 2007) in poultry birds exposed to heat stress.…”
Section: Erbca-2018-0915mentioning
confidence: 99%